2003
DOI: 10.1023/b:phot.0000011959.30746.c0
|View full text |Cite
|
Sign up to set email alerts
|

The Susceptibility of Cucumber and Sweet Pepper to Chilling Under Low Irradiance is Related to Energy Dissipation and Water-Water Cycle

Abstract: The photoprotection of energy dissipation and water-water cycle were investigated by comparing chilling sensitivity of photosystems 2 (PS2) and 1 (PS1) in two chilling-sensitive plants, cucumber and sweet pepper, upon exposure to 4 °C under low irradiance (100 µmol m -2 s -1 ) for 6 h. During chilling stress, the maximum photochemical efficiency of PS2 (F v /F m ) decreased only slightly in both plants, but the oxidisable P700 decreased markedly, which indicated that PS1 was more sensitive to chilling treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 35 publications
(45 reference statements)
5
74
0
Order By: Relevance
“…Under environmental stress, the photoinhibition took place mainly in PSII, which may be partly due to stressassociated oxidative damage to chloroplast components (Li et al 2003). In the present study, the V-to-Z conversion of the xanthophyll cycle played a more important role in preventing excessive ROS such as H 2 O 2 and O 2 Á-(Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Under environmental stress, the photoinhibition took place mainly in PSII, which may be partly due to stressassociated oxidative damage to chloroplast components (Li et al 2003). In the present study, the V-to-Z conversion of the xanthophyll cycle played a more important role in preventing excessive ROS such as H 2 O 2 and O 2 Á-(Figs.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the increased level of NPQ indicates that a photoprotective process of the PSII was taking place. We can suppose that the excitation pressure on PSII reaction centers is alleviated by the xanthophyll cycle diverting photon energy into heat via zeaxanthin (Gilmore et al 1995;Xu et al 1999;Li et al 2003;Sui et al 2007). The opening of stomata between 0 and 24 h of chilling could be related to the increase of NPQ.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies showed that chilling stress under low irradiance could cause the decrease of photosynthesis and photoinhibition of both photosystems, PS2 and PS1 (Li et al 2003(Li et al , 2004b. The maximal photochemical efficiency of PS2 (F v /F m ) and the oxidation level of P700 are often used to reflect the extent of photoinhibition of PS2 and PS1, respectively.…”
Section: Introductionmentioning
confidence: 94%